Characterization of tuber blight suppressive soils from four provinces of the Ecuadorean Andes - Orquera-Tornakian, G.; Díaz, C.I.; Mogrovejo, D.C.; Villamarin, D.J.; Jarrin, F.; Ponce, L.K.; Oliva, R.; Gia, J.; Forbes, G.; Flores, F.J.; Garzon, C.D.; Molineros, J.; et al. (Wiley, 2018)
Late blight, caused by the oomycete Phytophthora infestans, is a threat to potato cropping systems worldwide. In the Ecuadorian Andes, despite a high late blight incidence in foliage, tuber blight is rare. In this work, the hypothesis that Ecuadorian Andean soils are naturally suppressive to P. infestans tuber infection was evaluated. Soils from four potato growing regions were assessed for disease suppressiveness by determining the effects of soil heat treatment on P. infestans sporangia and their ability to infect potato slices after 1, 8, 15 and 30 days of exposure to soils. Tuber infection after inoculation with P. infestans infested soils was consistently lower during the evaluation period compared with heat treated soils. Fresh, untreated soils affected germination and viability of P. infestans sporangia in a site dependent manner. In addition, the effect of heat treatment on soil bacterial communities was assessed through terminal restriction fragment length polymorphism analysis of the 16S rDNA gene region. Heat treatment disrupted bacterial community composition, and a subset of terminal restriction fragments (TRF) was either positively or negatively correlated with tuber infection. Bacterial TRF negatively correlated with tuber infection corresponded in fragment size to taxa with known ability to inhibit pathogens and promote plant growth. Finally, bacterial isolates obtained from untreated soils, which inhibited P. infestans growth in vitro, represented 22–47% of isolates recovered, and matched classes predicted by the TRFs. This work represents a first step in understanding the mechanisms behind.